Microhardness and Elastic Properties Evaluation of WC-TiC Coatings Obtained by Arc Spraying Process - R. Haraga; D. Chicet; S. Toma; V. Carlescu; C. Bejinariu (Archives of Metallurgy and Materials)
Fulfilling the basic role of hard thermal sprayied coatings is closely related to the value of its microhardness. The quality of such a layer depends on several variables, the main categories being: spray method (flame spray, electric arc, plasma spray, cold spray, etc.), spray parameters (spray distance, voltage and intensity, working atmosphere, direction of the spray jet, etc.) and the materials used (chemical composition of the coating materials, quality and texture of the substrate). In this study, the microhardness, elastic properties and cohesion of a coating made of hard cored wire (Praxair – Tafa) by electric arc spraying process on a low alloy steel substrate, were analyzed. The cored wire has as main hard elements WC (about 26%) and TiC (about 6%), the rest of the chemical elements present being: Cr (14%), Ni (4.5%), B (1.87%), Si (1.25%) and the Fe balance. The micro-hardness was evaluated onto the surface of the coating, previously prepared by grinding to reduce the as-coated roughness. The method based on recording the forcess generated during the indentation with simultaneous measurement of the load – depth curve (with UMT 2MCETR microtribometer) were used for the microhardness evaluation. In order to analyse the cohesion of the coated layer, scratch tests with progressive loading (10N, 15N and 20N) were performed on the same microtribometer. Tests have shown that the metal matrix uniformly includes the hard particles arised from the core of the wire, and at the microstructural level, the microhardness varies significantly, depending on the hardness of the particles on which the indentor tip applies the loading forces. However, the overall behavior of the coatings thus realized is a satisfactory one, being, as a general behavior, in the average required by the applications of such a layer.